التجارة الإلكترونية في الجزائر: العقبات ومتطلبات التطوير - مع الإشارة إلى جائحة كوفيد-19- - زقرير, عادل; بالحبيب, عبد الكامل; مدوكي, يوسف (جامعة الوادي - University of Eloued, 2021)
تطور نشاط التجارة الإلكترونية حتى اكتسب مكانة أساسية بين الأنشطة الاقتصادية، خاصة في الدول المتقدمة، وهذا نظرا للمنافع التي يتيحها للأعوان الاقتصاديين على المستوى الجزئي والكلي. تهدف هذه الدراسة إلى تحليل واقع التجارة الإلكترونية في الجزائر من خلال تطور بنيتها التحتية التي تشمل تكنولوجيا الإعلام والاتصال، وكذا أهم الجهود المبذولة في سبيل تطوير بيئة التجارة الإلكترونية. علاوة على إبراز أهم العقبات التي تعوق تطور التجارة الإلكترونية وتحد من أهميتها في تجاوز صعوبات جائحة كوفيد-19. ومن أهم النتائج هي أن أكبر عقبة أمام ازدهار التجارة الإلكترونية في الجزائر يتمثل في الدفع الالكتروني، حيث إن جل التجارب في هذا المجال تعتمد على الدفع عند الاستلام أو التحويل البريدي. E-commerce activity has evolved until it has gained a primary place among economic activities, especially in developed countries, and this is due to the benefits it provides to economic agents at the micro and macro level. This study aims to analyze the reality of e-commerce in Algeria through the development of its infrastructure, which includes information and communication technology, As well as the most important efforts to develop ecommerce environment. In addition to highlighting the most important obstacles that hinder the development of ecommerce and limit its importance in overcoming the difficulties of the Covid19 pandemic. Among the most important results is that the biggest obstacle to the prosperity of e-commerce in Algeria is electronic payment, as most of the experiences in this field depend on payment on receipt or postal transfer
E-commerce in Algeria: Obstacles and development requirements –With referring to the Covid-19 pandemic --
مقال